Hubungan Pola Makan dengan Risiko Terjadinya Sindrom Ovarium Polikistik pada Remaja - Irene, Angela; Alkaf, Syifa; Zulissetiana, Eka Febri; Usman, Fatimah; Larasaty, Veny (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Polycystic Ovary Syndrome (PCOS) is the most common endocrine disorder in women with broad consequences that affect every aspect of a woman's life, with the incidence of PCOS in adolescents approximately 11-26%. More than 50% of PCOS patients are associated with metabolic syndrome including obesity, insulin resistance, and dyslipidemia. Studies said that diet plays an important role as a risk factor for PCOS in adolescents. Therefore the importance of dietary arrangements to improve hormonal disorders and long-term effects due to PCOS, so it is necessary to do further analysis of the relationship between eating patterns and the risk of PCOS occurrence in adolescents aged 15-19 years in the city of Palembang. This study was an observational study with a cross-sectional design. The data taken is primary data on adolescents aged 15-19 years in Palembang City. Retrieval of data intake on respondents was carried out with a food recall questionnaire, which is then for calorie and macronutrient calculations using nutrisurvey software. The diagnosis of PCOS is established by finding two of the three Rotterdam criteria. From a total of 150 samples, most with normal menstrual cycles, overweight/obese BMI, calorie intake, excess carbohydrate and fat consumption, adequate protein consumption, and less fiber consumption. There were 38 samples (25.3%) obtained with Polycystic Ovary Syndrome (PCOS). Samples that have PCOS, mostly with overweight/obese BMI (p <0.05), calorie intake, consumption of carbohydrates, protein, excess fat (p<0.05), and less fiber consumption (p>0.05). There is a significant relationship between calorie intake, consumption of carbohydrates, protein, and excess fat, as well as less fiber consumption and the risk of Polycystic Ovary Syndrome (PCOS) in adolescents aged 15-19 years in the city of Palembang.